THE REFOULEMENT PRINCIPLE AND ITS RELEVANCE IN THE INTERNATIONAL LAW SYSTEM - Riyanto, Sigit (UI Scholars Hub, 2010)
The principle of Non-Refoulement is a concept that is very well known in the framework of international protection applicable to refugees and or asylum seekers. Non Refoulement is a concept in which State shall not expel or return (“refouler”) a refugee or asylum seeker in any manner whatsoever to the frontiers of territories where his life or freedom would be threatened on account of his race, religion, nationality, membership of a particular social group or political opinion. The principle of Non Refoulement is generally relevant to the protection of human rights, especially in relation with the freedom of torture or cruel, inhuman or degrading treatment or punishment. In the context of international refugee law, the principle of Non Refoulement is a fundamental concept and considered as the back-bone of the whole frameworks of international protection for refugee and asylum seeker. This article discussed three aspects relevant to the principle of Non Refoulement, namely : the existence of such a principle in the existing international legalsystem, the character of the principle of Non Refoulement as Jus Cogens, and the condition of which the benefit of such a principle may not be applied. It is obvious that the principle of Non- Refoulement has been accepted by international community as explicitly established in international legal instruments and consistently implemented in the practice of State and the relevant international organisations. Such a principle is accepted by international community and gained ground as Jus Cogens in the international legal system, consequently States individually or collectively shall not derogate in a manner whatsoever, otherwise it is modified by a subsequent norm of general international law having the same character.However, should there are reasonable grounds, the benefit of the present principle may not be granted to a refugee.